Transcutaneous electrical acupoint stimulation combined with electroacupuncture promotes rapid recovery after abdominal surgery: Study protocol for a randomized controlled trial - Li, Hao; Du, Chen; Lu, Lingyun; Hu, Xiangyun; Xu, Huiming; Li, Ning; Liu, Hong; Wen, Qian (Frontiers in Public Health, 2022)
Introduction The most frequent complications after abdominal surgery include a decrease or loss of appetite, abdominal distension, abdominal pain caused by reduced gastrointestinal motility, anal arrest with intestinal distension and defecation, and nausea and vomiting due to anesthetic and opioid analgesic administration. These complications severely affect postoperative recovery, prolong hospital stay, and increase the financial burden. The objective of this study is to investigate the efficacy and safety of three acupoint stimulation modalities (electroacupuncture [EA], transcutaneous electrical acupoint stimulation [TEAS], and transcutaneous acupoint electrical stimulation combined with EA [TEAS+EA]), and two EA instrument waveforms (continuous wave and dilatational wave) for rapid recovery after abdominal surgery. Methods and analysis A total of 560 patients will be recruited and randomly allocated to receive one of the following seven interventions: continuous wave EA, continuous wave TEAS, continuous wave TEAS + EA, dilatational wave EA, dilatational wave TEAS, dilatational wave TEAS + EA, and a control. For this study, continuous waves at 2 Hz, and dilatational waves at 2/50 Hz would be selected. The points to be stimulated by EA are the bilateral Neiguan (PC6), Hegu (LI6), Zusanli (ST36), Shangjuxu (ST37), and Xiajuxu (ST39), and TEAS would stimulate the bilateral Liangmen (ST21) and Daheng (SP15). The control group will neither receive EA nor TEAS. All patients will undergo an enhanced recovery plan after surgery and be provided with standardized perioperative management. Treatment will start on the first postoperative day and be administered once daily in the morning until the patient regains spontaneous bowel movements and can tolerate oral intake of solid food. The primary outcome is a composite of time to first defecation and time to tolerance of a solid diet. Secondary outcomes include time to first exhaustion; time of first defecation; time of tolerance of a solid diet; time to the first ambulation; length of hospital stay from surgery to discharge; visual analog scale score for postoperative daily pain, nausea, and vomiting; incidence of postoperative complications; and treatment acceptability. Discussion This study will compare the efficacy and safety of three acupoint stimulation methods and two EA instrument waveforms for rapid recovery after abdominal surgery. Trial Registration Chinese Clinical Trial Registry (http://www.chictr.org.cn), ChiCTR2100043883.